A method for the determination and correction of the effect of thermal degradation on the viscoelastic properties of degradable polymers - Choong, Gabriel Y. H.; De Focatiis, Davide S.A. (Elsevier, 2016)
Small amplitude oscillatory shear is carried out during isothermal degradation of poly(lactic acid) (PLA) in order to determine the evolution of the characteristic relaxation time with degradation time and temperature. After reducing the relaxation time data to a single mastercurve, a 4-parameter function is fitted to the data to allow prediction of the change in relaxation time following an arbitrary thermal history. The method enables separation of the effects of temperature and of degradation on the relaxation time, both of which lead to a horizontal shift of dynamic data along the frequency axis, and hence enable a correction for thermal degradation during rheometry to be carried out. To validate the method, two isothermal frequency sweeps were measured with different temperature histories, producing different mastercurves due to dissimilar in-test thermal degradation. After correcting for thermal degradation using the function and the thermal histories, the two frequency sweeps reduce to the same viscoelastic mastercurve in the undegraded pre-test state.